Intelligent systems : principles, paradigms, and pragmatics - Schalkoff, Robert J. (Jones and Bartlett Publishers, 2011)
"Intelligent Systems: Principles, Paradigms and Pragmatics takes a modern, 21st century approach to the concepts of Artificial Intelligence and includes the latest developments, developmental tools, programming and approaches related to AI."-- BOOK JACK